Relationship between disease course in the temporomandibular joints and mandibular growth rotation in patients with juvenile idiopathic arthritis followed from childhood to adulthood - Flatø B; Smith H-J; Arvidsson LZ; Fjeld MG; Øgaard B; Larheim TA (BMC, 2010)
Abstract Objective To investigate the relationship between radiographic JIA disease course in the TMJs and mandibular growth rotation, compared with growth in healthy individuals. Methods From a larger series of JIA patients followed from childhood to adulthood, 26 were included; 11 without and 15 with bilateral radiographic TMJ involvement. Joint morphology and function were assessed at baseline, 2-, 4-, 6- and 27 years follow-up. Mandibular growth rotation (anterior, posterior or none) was assessed from cephalometric evaluations at childhood and adulthood, with observations from 16 healthy individuals as controls. TMJ disease course and mandibular growth rotation were assessed independently and their relationship analysed. Non-parametric statistical methods were applied to test differences between groups. Results In the normal TMJ group of JIA patients the joint morphology was similar at the follow-ups and all patients had good function both in childhood and in adulthood. The mandibular growth rotation was similar to that of healthy controls, i.e. predominantly in anterior direction. In the abnormal TMJ group different JIA TMJ disease courses were observed and associated with changes in the mandibular growth rotation (p = 0.007). Progressing JIA TMJ disease course was related to posterior mandibular growth rotation and improving disease course to anterior mandibular growth rotation. Conclusion A relationship was found between JIA disease course in the TMJs and mandibular growth rotation, suggesting that a favourable growth could be regained in patients with improvement in TMJ morphology and/or TMJ function. To confirm this, further research on larger patient series is needed.